The PENGARUH PERTUMBUHAN EKONOMI, INVESTASI DAN PENGELUARAN PEMERINTAH TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI SULAWESI UTARA - Rompas, Wensy (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
The study aims to determine the effect of economic growth on labor absorption in North Sulawesi Province, the effect of investment on labor absorption in North Sulawesi Province, the effect of government spending on labor absorption in North Sulawesi Province and the effect of economic growth, investment and government spending on labor absorption in North Sulawesi Province. This type of research is quantitative research with an associative approach. The data analysis technique in this study is multiple linear regression. The results of the study indicate that there is a significant effect of economic growth on labor absorption in North Sulawesi Province, there is a significant effect of investment on labor absorption in North Sulawesi Province, there is a significant effect of government spending on labor absorption in North Sulawesi Province and there is a significant effect of economic growth, investment and government spending on labor absorption in North Sulawesi Province